Management of the organization and personnel support for clustering of innovative development - Стелюк, Барбара Борисівна; Козинец, Виктор Павлович; Сиволап, Татьяна Николаевна (Eastern-European Journal of Enterprise Technologies, 2010)
The innovative model of technological development was considered. Stages of innovative process taking into account interaction of strategic and operative marketing are presented during management of innovations. Features of management technological clustering and professional trainings of innovative development of Ukraine are allocated.